Metabolic syndrome as a clinical manifestation of endothelial dysfunction - L. L. Kirichenko; K. V. Ovsyannikov; A. N. Fedoseev; A. M. Shklyarov; A. P. Korolev (Кардиоваскулярная терапия и профилактика, 2012)
Metabolic syndrome (MS) has recently gained more clinical attention due to its increasing prevalence and association with adverse prognosis. One of the main pathological features of MS is endothelial dysfunction. It plays a key role in the development of cardiovascular MS complications. Therefore, effective therapy aimed at the normalization of endothelial function should be a part of pathogenetic management of MS patients.